The Effect Of Perceived Cost, Perceived Ease, and Perceived Security on The Choice of Interbank Transfer Platforms among Students at Nurul Jadid University - Khotija; Rizki Febri Eka Pradani (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to examine the influence of perceived cost, perceived ease of use, and perceived security on the choice of interbank transfer platforms among students in the Economics Program at Nurul Jadid University. The study employs a quantitative method with an associative approach. The population consisted of 356 active students from the 2022–2025 cohorts, with a sample of 185 respondents determined using the Isaac and Michael formula through non-probability sampling. Data were collected via a 1–4 Likert-scale questionnaire distributed through Google Forms and analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) with the aid of IBM SPSS Statistics Version 25. The results indicate that: (1) cost perception has a positive and significant effect on platform selection (t = 5.300 > 1.973; sig. = 0.000 < 0.05); (2) perceived ease has a positive and significant effect (t = 4.630 > 1.973; sig. = 0.000 < 0.05); (3) perceived security has a positive and significant effect and exerts the greatest influence (t = 5.743 > 1.973; sig. = 0.000 < 0.05); and (4) all three variables simultaneously have a positive and significant effect (F = 126.617 > 2.65; sig. = 0.000 < 0.05). The adjusted R² value of 0.672 indicates that these variables explain 67.2% of the variation in platform choice, while the remaining 32.8% is influenced by other factors. These findings confirm that cost, convenience, and security are the primary determinants in the choice of interbank transfer platforms.